Hot-wire anemometry measurements of collared-jets - Tay, Travis Yi Sheng. (2013)
The purpose of this project is to conduct an experimental investigation using hot-wire anemometry to understand the effects of collared jet nozzles on jet flow. The collars used are namely circular, squared and triangular collared jets. Each collar shape can be altered in collar length for in depth analysis. Experiments are conducted in both stream wise and cross stream direction. The experimental data collected can be used to analyse centreline velocity decay, centreline turbulent intensity, virtual origin and cross stream velocity profile. The experimental results showed that triangular collared jet has the best centreline velocity decay and perhaps the most gradual cross stream velocity profile due to a higher expansion ratio compared with circular and squared collars. A higher expansion ratio would mean that there is an increased self-excitation in flow behaviour, hence aiding in jet mixing.